2020
DOI: 10.32655/libres.2020.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the quality of work life of librarians in public libraries based on organizational justice dimensions

Abstract: Background. Human resources are considered the most significant assets of any organization. Improving the quality of work life will motivate employees to provide quality services. Objective. This study investigated the extent to which organizational justice and its dimensions affect perception of the quality of work life among librarians working in the public libraries of Iran. Organizational justice refers to employees' apprehension of the extent that management's actions and decisions are fair and equitable.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The study further, confirmed that the work-life quality of IPs is significantly related to gender, age, institution type and experience but not an educational qualification of Nigerian librarians (Anyaoku, 2016). Jahangiri et al (2020) studied academic librarians' QoWL of Iran and found a significant positive relationship between QoWL and organizational justice. Previously, Kohhbanani et al (2019) reported that Irani public librarians are moderately satisfied with growth opportunities, safe and healthy work environment, whereas their level of satisfaction with salary, the social relevance of work-life and total life space was low.…”
Section: Information Professionals'mentioning
confidence: 58%
See 1 more Smart Citation
“…The study further, confirmed that the work-life quality of IPs is significantly related to gender, age, institution type and experience but not an educational qualification of Nigerian librarians (Anyaoku, 2016). Jahangiri et al (2020) studied academic librarians' QoWL of Iran and found a significant positive relationship between QoWL and organizational justice. Previously, Kohhbanani et al (2019) reported that Irani public librarians are moderately satisfied with growth opportunities, safe and healthy work environment, whereas their level of satisfaction with salary, the social relevance of work-life and total life space was low.…”
Section: Information Professionals'mentioning
confidence: 58%
“…Jahangiri et al. (2020) studied academic librarians' QoWL of Iran and found a significant positive relationship between QoWL and organizational justice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to distributive justice, the concept of justice can also be seen from the value of procedural justice [13]. The procedural fairness revealed relates to the perceived conformity of all employees, particularly lecturers, that use it for undergoing work procedures, achieving achievements, and career advancement [14].…”
Section: Introductionmentioning
confidence: 99%
“…Este resultado está de acordo com pesquisas anteriores já realizadas e que tiveram a mesma percepção, como por exemplo no estudo de Aminbeidokhti e Mardani (2014), os quais estudaram a mesma relação em um hospital iraniano. Para explicar o achado os autoresJahangiri et al (2020) apontam que a qualidade de vida no trabalho é influenciada por diversos fatores como por exemplo, horário de expediente, instalações inadequadas, práticas gerenciais, falta de oportunidade para o progresso entre outros, sendo estes pontos identificados no modelo deWalton (1973).Percebeu-se que pelo objetivo central do estudo que os autores buscam identificar dois elementos distintos, ou seja, qualidade de vida no trabalho e justiça organizacional, sendo aplicado o modelo de Walton de maneira complementar tendo em vista que este de forma isolada não atende as necessidades para uma análise completa, pois de acordo com os objetivos dos autores o questionário de Walton não avalia a tomada de decisões dos gestores e que tais decisões podem afetar positiva ou negativamente a QVT.O estudo a seguir teve como ponto central desenvolver uma revisão sistemática e meta análise da Qualidade de Vida no Trabalho, no Irã, no período de (2011-2017), elaborado por Sanagoo, Sarokhani, Dehkordi, Sayehmiri e Jouybari (2020), tendo como objetivo central estimar a QVT de acordo com diferentes escalas, componentes, sexo, emprego, cidade e estado civil no Irã. Os procedimentos metodológicos adotados para alcançar o objetivo se deram pela realização de uma revisão sistemática conduzida por uma revisão dos artigos publicados no período de 2011-2017, para acessar os documentos no Irã foram realizadas buscas nas bases de dados nacionais e internacionais como Science Direct, Pubmed, Scopus, Web of Science entre outras, através do uso de palavras-chave nas bases de dados internacionais quality of work life, score of quality of work life, meta-analysis e Irã usando os operadores "AND/OR.…”
unclassified